Optimización de la planta de tratamiento de aguas residuales del proceso operativo en el patio de comidas del Centro Comercial “Malteria Plaza”, cantón Latacunga, provincia de Cotopaxi - Calvopiña Mullo Janeth Marisol, Mayorga Bonilla Carlos Andrés (2018)
This research project will be carried out in order to comply with the permissible limits of quality parameters of wastewater to be discharged into a freshwater receiving body, for which physical and chemical treatment processes will be used to help reduce of these polluting substances of the water resource. Thus contributing to the care and protection of the environment, as established by the constitution of Ecuador in Section Two Art 14.- The right of the population to live in a healthy and ecologically balanced environment is recognized, which guarantees sustainability and good living, Sumak kawsay.